PRIMARY CLASSES - Berdiyarova Zarbibi Eshtemir 's Daughter (Galaxy International Interdisciplinary Research Journal, 2022)
This article presents a new national program in primary grades. The positive aspects, including the importance of mother tongue and reading literacy , are discussed in terms of teaching trends, goals, and expected results based on the national curriculum . In this regard , the shortcomings and achievements are the requirements and plans.